Glycolic acid-g-chitosan-gold nanoflower nanocomposite scaffolds for drug delivery and tissue engineering - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2012)
This paper reports a simple novel method for the synthesis of flower like gold nanoparticle (three dimensional branched nanoparticle) with >30 tips, under controlled temperature condition. Formation of flower like Au nanoparticle was confirmed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Next step of this paper reveals the potential use of novel hybrids of chitosan-g-glycolic acid and gold nanoflower (AuNF) in controlled drug delivery and tissue engineering applications. The drug loaded novel nanohybrid scaffold is prepared by freeze drying of grafted polymer solution. Grafting of glycolic acid to the chitosan and incorporation of drug were evaluated by Fourier transform infrared spectroscopy (FTIR). The nanohybrid scaffolds were found to be stable towards the pH of the medium. The cell viability study shows that prepared nanohybrid scaffolds are biocompatible. Gold nanoflowers were found to control the drug release rate in the buffer solution (pH 7.4). Therefore, for the glycolic acid grafted chitosan based system, gold nanoflowers are the viable additive for drug delivery. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chitosan; Drug delivery system; Glycolic acid grafting; Gold nanoflower; Nanocomposite

Glycolic acid-g-chitosan-Pt-Fe3O4 nanoparticles nanohybrid scaffold for tissue engineering and drug delivery - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2012)
This work presents the potential use of novel nanohybrid based on chitosan-g-glycolic acid and Pt-Fe3O4 composite nanoparticles in drug delivery and tissue engineering applications. The Pt-Fe3O4 hybrid nanoparticles are prepared by thermal decomposition of H2PtCl6 center dot 6H(2)O at high temperature. The prepared nanoparticles were characterized by transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and physical property measurement system (PPMS). Next step of this paper reveals the potential use of novel hybrids of chitosan-g-glycolic acid and Pt-Fe3O4 hybrid nanoparticles in controlled drug delivery applications. The drug loaded nanohybrid scaffold is prepared by freeze drying of grafted polymer solution. Drug loading and grafting of chitosan was characterized by Fourier transform infrared spectroscopy (FTIR). The cell proliferation also shows that the prepared nanohybrids are biocompatible. The nanohybrid was found to be stable regardless of pH of the medium. Therefore, Pt-Fe3O4 hybrid nanoparticles are viable additive for sustained drug delivery and it could be applied in the field of biomedical. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Cell viability; Chitosan; drug delivery; Glycolic acid grafting; Pt-Fe3O4 hybrid nanoparticle

Glycolic acid functionalized chitosan-Au-Fe3O4 hybrid nanoparticle based nanohybrid scaffold for drug delivery - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2013)
The research on biomedical applications of nanoparticles has seen an upsurge in recent years due to their unique capabilities in treatment of ailments. The present paper reports the synthesis of Au-Fe3O4 hybrid nanoparticles. The formation of these nanoparticles was confirmed by transmission electron microscopy (TEM) and physical property measurement system (PPMS). Next step of this paper reveals potential use of novel hybrid of chitosan-g-glycolic acid and Au-Fe3O4 hybrid nanoparticles in controlled drug delivery and tissue engineering applications. Grafting of glycolic acid and drug loading in porous scaffold was characterized by Fourier transform infrared spectroscopy. The nanohybrid scaffolds were found to be stable regardless of pH of the medium and play a key role in cell adhesion, proliferation and migration. Au-Fe3O4 hybrid nanoparticles reinforcement was found to control the drug (cyclophosphamide) release rate in phosphate buffer saline solution (pH 7.4). Therefore, Au-Fe3O4 hybrid nanoparticles are viable additive for formulating sustained drug delivery systems based on glycolic acid grafted chitosan. The cell proliferation profile also shows that prepared nanohybrid is biocompatible providing suitable substrates for tissue engineering. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Au-Fe3O4 hybrid nanoparticles; Chitosan Glycolic acid grafting; Drug delivery system; Physical property measurement system

Glycolic acid-functionalized chitosan-Co3O4-Fe3O4 hybrid magnetic nanoparticles-based nanohybrid scaffolds for drug-delivery and tissue engineering - Kumari, Sangeeta; Singh, Raj Pal (Journal of Materials Science, 2013)
In the present work, Co3O4 was prepared by hydrothermal process, which is further used for the synthesis of Co3O4-Fe3O4 hybrid nanoparticles. The formation of Co3O4-Fe3O4 nanoparticles was investigated by transmission electron microscopy and physical property measurement system. In the next step, the drug-loaded novel nanohybrid porous scaffold based on chitosan-g-glycolic acid and Co3O4-Fe3O4 nanoparticle was prepared by freeze drying technique. The grafting of glycolic acid on chitosan drug loading in porous scaffold was characterized by Fourier transform infrared spectroscopy. The nanohybrid scaffolds were found to be stable regardless of the pH of the medium and play an important role in cell adhesion, proliferation, and migration. Co3O4-Fe3O4 hybrid nanoparticles' reinforcement was found to control the drug (cyclophosphamide) release rate in phosphate buffer saline solution (pH 7.4). Therefore, Co3O4-Fe3O4 hybrid nanoparticles are viable additives for formulating sustained drug delivery systems and could be applied in the field of biomaterials.

Chitosan-based bionanocomposites for biomedical application - Kumari, Sangeeta; Singh, Raj Pal; Chavan, Nayaku N.; Annamalai, Pratheep K. (Bioinspired Biomimetic and Nanobiomaterials, 2018)
Natural polymers have greatly impacted the advancement of modern medicine. Natural polymer-based biomaterials are biodegradable. A significant advantage of natural polymers is that they can be broken down and removed from the body after they have served their function. A wide range of novel biomaterials from natural polymers has been investigated to meet new challenges in medical science. Chitosan is one of the natural polymers which have been widely used in the biomedical field. Nanotechnology is one of the most popular areas of current research. In the area of nanotechnology, polymer and metal/metal oxide nanoparticle matrix-based nanocomposites have generated a significant amount of attention in the recent literature. These bionanocomposites have wide-ranging applications in drug delivery and tissue engineering. This paper discusses polymer-metal/metal oxide nanoparticle matrix-based nanocomposite biomaterials and their applications in the biomedical field - that is, drug delivery and tissue engineering applications.

Characterization of a novel nanocomposite film based on functionalized chitosan-Pt-Fe3O4 hybrid nanoparticles - Kumari, Sangeeta; Singh, Raj Pal; Chavan, Nayaku N.; Sahi, Shivendra V.; Sharma, Nilesh (Nanomaterials, 2021)
The development of organic-inorganic hybrids or nanocomposite films is increasingly becoming attractive in light of their emerging applications. This research focuses on the formation of a unique nanocomposite film with enhanced elasticity suitable for many biomedical applications. The physical property measurement system and transmission electron microscopy were used to analyze Pt-Fe3O4 hybrid nanoparticles. These nanohybrids exhibited magnetic effects. They were further exploited to prepare the nanocomposite films in conjunction with a chitosan-g-glycolic acid organic fraction. The nanocomposite films were then examined using standard techniques: thermogravimetric analysis, X-ray diffraction, Fourier transform infrared spectroscopy, and atomic force microscopy. Tensile strength testing demonstrated a significantly greater elastic strength of these nanocomposite films than pure chitosan films. The water absorption behavior of the nanocomposites was evaluated by measuring swelling degree. These nanocomposites were observed to have substantially improved physical properties. Such novel nanocomposites can be extended to various biomedical applications, which include drug delivery and tissue engineering.
Keywords: Chitosan; nanocomposite films; Pt-Fe3O4 hybrid nanoparticles; tensile strength testing; Thermogravimetric analysis

Zn(ii)-metallo-photoantibiotics: experimental and computational approach identifying a therapeutic role for antibacterial and antibiofilm applications - Kushwaha, Rajesh; Kumari, Sangeeta; Mishra, Arya; Upadhyay, Anjali; Rai, Archana; Nayak, Malay; Mukherjee, Sudip; Banerjee, Samya (Chemical Communications, 2025)
The antibacterial profiles of curcumin-based novel Zn(ii)-metallo-photoantibiotics against E. coli and B. subtilis are reported. In silico studies indicated their ROS generation capacity and binding interaction with bacterial proteins. Therapeutic results indicated the advantages of these Zn(ii)-metallo-photoantibiotics in antibacterial photodynamic therapy.